Electrical system for 41-storey Torre De Manila Bldg at Taft Avenue, Ermita, Manila, Philippines - Suelto, Edison R. (Manila Professional Regulation Commission, 2015)
Torre de Manila is a condominium project of DM Consunji Inc. (DMCI). In June 2012, DMCI managed to secure a zoning permit that allows the company to build the Torre de Manila in a lot along Taft Avenue. The planned location of the building is behind the lot previously occupied by the Manila Jai Alai Building. The following month, the Manila city government under Mayor Alfredo Lim, granted a building permit to DMCI The electrical system design for this high rise building at Taft Avenue, Ermita, Manila, Philippines is consisting of 4 - Low Voltage Switchgear CLVSG) connected from - 7S0KVA, 34.SKV-Y/ 41SV-Y, 3-PHASE, 60HZ and synchronized to 4 - 7S0KVA, 400V-Y, 3-PHASE, 60HZ diesel generator set.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-676G donated by Mr. Jaime V. Mendoza.
Keywords: Buildings -- Electric equipment